PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENYEBARAN PROMOSI INVESTASI MENYESATKAN PADA PLATFORM BINARY OPTION DALAM PERSPEKTIF UU ITE NO. 19 TAHUN 2016 - Ramadhana, Widodo; Chew, Andrew; Irwanda, Irwanda (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Many people are tempted to take part in trading due to the presence of affiliates, influencers or public figures in promoting Binomo as an investment platform. For this reason, it is necessary to study the forms of misleading investment promotion and the criminal responsibility of perpetrators who promote misleading investment products on the binary options platform. The type of research is normative law. The nature of research is descriptive analysis. Data collection techniques use library searches. Data analysis was carried out qualitatively. A misleading form of investment promotion is carried out by showing the profits obtained along with the luxuries resulting from trading to attract target customers. This violates the provisions of Article 10 UUPK and Article 28 paragraph (1) UU ITE which states: "anyone who intentionally and without right spreads false and misleading news which results in consumer losses in electronic transactions." The criminal liability of perpetrators who promote misleading investment products on the binary options platform may be subject to criminal sanctions as stipulated in Article 27 paragraph (1) and Article 28 (1) in conjunction with Article 45A (1) of the ITE Law.